The Influence of Work Motivation and Work Environment on Organizational Citizenship Behavior with Job Satisfaction as an Intervening Variable in the DIY Tourism Office - Susanti, Ndari; Siswanti, Yuni; Ambarwati, Sri Dwi Ari (CV. Strata Persada Academia, 2025)
This study examines the influence of work motivation and work environment on Organizational Citizenship Behavior (OCB) with job satisfaction as an intervening variable among employees of the Yogyakarta Special Region (DIY) Tourism Office. Using a quantitative approach, data were collected from 74 employees through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 2.0. The results show that work motivation and work environment have a positive and significant effect on OCB, and job satisfaction mediates these relationships, indicating that employees who feel satisfied with their work are more likely to engage in voluntary behaviors beyond formal job duties. These findings highlight the importance of intrinsic and extrinsic motivation and a supportive work environment in fostering positive employee attitudes and extra-role behavior that enhance organizational performance. Theoretically, the study clarifies the mediating role of job satisfaction in the relationship between work motivation, work environment, and OCB within a public tourism context, while practically providing insights for public institutions to strengthen human resource policies that encourage proactive, cooperative, and high-performing behavior. Future studies are recommended to include additional variables such as organizational culture and leadership style to deepen understanding of OCB dynamics.